Improving Sixth-Grade Students’ Cognitive Achievement in Mathematics through the Teams Games Tournament (TGT) Cooperative Learning Model at SDN kemayoran 2 - Dina Mulyana Firdausiyah; Selvia Dwiyanti; Feni Aprilliyah; Erika Zakiah Sholiha; Nurhidayah Nurhidayah (Literasi Nusantara, 2026)
This study was conducted to address the low mathematics learning achievement of sixth-grade students at SDN Kemayoran 2. It aimed to describe the implementation of the Teams Games Tournament (TGT) cooperative learning model and examine its effectiveness in improving students’ cognitive learning achievement. The study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, involving 29 sixth-grade students in two cycles. Data were collected through observations, interviews, documentation, and achievement tests. The results showed a consistent improvement in learning mastery, increasing from 54.6% in the pre-cycle to 72.4% in Cycle I and 84.3% in Cycle II. These findings indicate that the TGT cooperative learning model effectively improved students’ cognitive mathematics achievement and classroom participation.